Determination of trace Mn(II) in pharmaceutical diet supplements by cathodic stripping voltammetry on bare carbon paste electrode - Rievaj, M; Tomcik, P; Janosikova, Z; Bustin, D; Compton, R (2008)
A simple electroanalytical method for quantification of Mn in pharmaceutical diet supplements has been developed. The method is based on the formation of insoluble MnO2 on the electrode during deposition step at the potential of +0.85V vs SCE, and its consecutive reductive dissolution back to Mn(II) during differential pulse voltammetry scan. Pure carbon paste was found to be a suitable material for this kind of determination because of its easy preparation, good accessibility, low cost, as well as its appropriate analytical properties. In 0.1 mol L-1 phosphate buffer (pH 7.4) supporting electrolyte and at optimised deposition time (120 s) the linear calibration plot was obtained in the concentration range 1 × 10 -6-12 × 10-6 mol L-1; the corresponding detection limit was 1 × 10-7 mol L-1. The method was applied to the analysis of pharmaceutical dosage forms containing manganese as an essential trace element.